La polysémie nominale événement/ objet: Quels objets pour quels événements? - Barque, Lucie; Haas, Pauline; Huyghe, Richard (Neophilologica, 2014)
This paper deals with the lexical notion of event. We study the well-known event/object nominal polysemy (see Grimshaw, 1990; Pustejovsky, 1995; Godard, Jayez 1996, among others) and give it an exhaustive treatment by gathering many data from existing lexical resources. About 200 nouns are listed, with various morphological properties — simple, converse or derived nominal may be concerned. We identify different types of events (activity, accomplishment, etc.) and objects (artifact, place, etc.), based upon explicit linguistic criteria. Then we study the relations between the different meanings of event/object polysemous nouns and the conditions under which their semantic types can combine.